Activity 04 Skills audit exercise : student - UK Physical Sciences Centre; University of Hull; Grice, Della (The University of Hull)
This resource is student activity 4 as part of a broader resource called the Employability Resource Pack. There is a brief tutor guide to accompany this resource.